First observations on wall plasma expansion and x-ray flux in foam hohlraum at 100 kJ laser facility - Lu Zhang; Zhiwei Lin; Longfei Jing; Jianhua Zheng; Qiangqiang Wang; Sanwei Li; Zhurong Cao; Yunsong Dong; Bo Deng; Liling Li; Hang Li; Yulong Li; et al. (Matter and Radiation at Extremes)
The first experiments on laser-driven cylindrical gold foam hohlraums have been performed at the 100 kJ SG-III laser facility. Measurements of the expanding plasma emission show that there is less expanding plasma fill in foam hohlraums with a wall density of 0.8 g/cm3 than in solid gold hohlraums. The radiation temperatures at different angles confirm these results. Simulation results show that the expanding plasma density in the foam hohlraums is lower than in the solid hohlraums, resulting in less expanding plasma emission and higher radiation temperature. Thus, foam gold hohlraums have advantages in reducing wall plasma filling and improving X-ray transmission, which has potential applications in achieving a higher fusion yield.